Supplementary materials for: Mental health status of health care workers during the COVID-19 outbreak: An International Study - Nicolaou, Christiana; Menikou, Joanna; Lamnisos, Demetris; Kassianos, Angelos P.; Karekla, Maria; Gloster, Andrew T. (My University, 2021)
The COVID-19 pandemic is a massive health crisis which has brought enormous physical and psychological pressure. Mental health care for health care workers (HCWs) should receive serious consideration. The aim of this study was to determine the mental health outcomes of 1556 HCWs from 45 countries who participated in the COVID-19 IMPACT project and to examine the predictors of the outcomes during the first pandemic wave. Outcomes assessed were self – reported perceived stress, depression symptom, and sleep changes. Predictors examined included sociodemographic factors and perceived social support. Results demonstrated that half of the HCWs had moderate levels of perceived stress and symptoms of depression. Half of the HCWs (n=800, 51.4%) had similar sleeping patterns since the pandemic started and one in four slept more or slept less. HCWs reported less perceived stress and depression symptoms and higher levels of perceived social support than the general population who participated in the same project. Predictors associated with higher HCWs’ perceived stress and symptoms of depression included gender status female, not having children, living with parents, lower educational level, and having lower social support. The need for establishing ways to mitigate mental health risks and adjusting psychological interventions and support for HCWs seems to be significant as the pandemic continues.